Utilizing the Gravity Method to Detect the Potential Effect of the Salt Dome in the Nahr Omar Oilfield, Southern Iraq - Al-Inizi, Athir J.; Al-Saadi, Osamah S. (Iraqi Journal of Science, 2024)
Geophysics is one of the branches of Earth sciences and deals with studying the Earth's interior by studying the variation of physical properties within rock layers. Applied geophysics depends on procedures that involve the measurements of potential fields, such as the gravitational method. One of the significant oil fields in southern Iraq is represented by the Nahr Omar structure. A power spectrum analysis (SPA) technique was used to collect gravity data within the chosen oil field area in order to confirm the salt dome in the subsurface layers. The analysis of SPA resulted from six surfaces representing the gravity variation values of the depths (m)14300, 3780, 3290, 2170, 810, and 93.5. Gravity surfaces have been converted to density surfaces to determine density and velocity models from these six depth slices. The inverted data were consistent with the Nafe and Drake standard curves of converting densities to average velocities. The current study illustrated the benefit/assist of the inversion technique of gravity data to average velocity, to a large extent, in detecting the salt dome effects on the subsurface strata for the Nahr Omar oilfield. In comparison, the decrease in the average velocity of the salt dome area is related to this effect. The acquired inversion results were supported by available seismic data within the Nahr Omar area and utilized the seismic attributes processing technique.